NAVIGATING THE GREY AREAS: ADOLESCENT CONSENT, ROMANTIC RELATIONSHIPS AND THE POCSO ACT, 2012 IN INDIA - Dawda, Netra V.; Fadnavis, Snehal S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper explores the complex challenges posed in the implementation of the Protection of Children from Sexual Offences (POCSO) Act, particularly its impact on adolescent romantic relationships. It examines the unintended consequences of criminalizing all sexual behavior under the age of 18, despite developmental and consensual distinctions among teenagers. The study analyses how the rigid structure of the POCSO Act disproportionately affects adolescents engaged in consensual relationships and the broader societal and institutional implications of these legislative choices. Using a doctrinal methodology, the paper scrutinizes the POCSO Act’s framework, focusing on its mandatory reporting requirements, age determination challenges, and lack of differentiation between consensual and non-consensual acts. The analysis identifies gaps in enforcement, resource limitations, and cultural barriers that hinder effective protection and justice for children. The core argument advanced is that the current binary approach to the age of consent fails to account for adolescent autonomy and can result in miscarriages of justice for both victims and accused teenagers. The paper concludes that legal reform is imperative, recommending a nuanced adjustment to the age of consent provisions, early case screening to distinguish consensual acts, enhanced training for professionals, and greater stakeholder engagement in legislative revision. A multidimensional, society-wide approach—beyond mere legal frameworks—is essential to truly protect children while balancing their developmental rights.